“The Octet”: Eight Protein Kinases that Control Mammalian DNA Replication - Depamphilis, Melvin L.; de Renty, Christelle M.; Ullah, Zakir; Lee, Chrissie Y. (Frontiers in Physiology, 2012)
Development of a fertilized human egg into an average sized adult requires about 29 trillion cell divisions, thereby producing enough DNA to stretch to the Sun and back 200 times (DePamphilis and Bell, 2011)! Even more amazing is the fact that throughout these mitotic cell cycles, the human genome is duplicated once and only once each time a cell divides. If a cell accidentally begins to re-replicate its nuclear DNA prior to cell division, checkpoint pathways trigger apoptosis. And yet, some cells are developmentally programmed to respond to environmental cues by switching from mitotic cell cycles to endocycles, a process in which multiple S phases occur in the absence of either mitosis or cytokinesis. Endocycles allow production of viable, differentiated, polyploid cells that no longer proliferate. What is surprising is that among the 516 (Manning et al., 2002) to 557 (BioMart web site) protein kinases encoded by the human genome, only eight regulate nuclear DNA replication directly. These are Cdk1, Cdk2, Cdk4, Cdk6, Cdk7, Cdc7, Chk1 and Chk2. Even more remarkable is the fact that only four of these enzymes (Cdk1, Cdk7, Cdc7 and Chk1) are essential for mammalian development. Here we describe how these protein kinases determine when DNA replication occurs during mitotic cell cycles, how mammalian cells switch from mitotic cell cycles to endocycles, and how cancer cells can be selectively targeted for destruction by inducing them to begin a second S phase before mitosis is complete.